Risk of Coronary Artery Disease and Thigh Circumference - Akram, Ishwah; Zubair, Muhammad; Bukhari, Syeda Kinza; Khan, Fahad Ahmad; Maheen, Aima; Aslam, Bareera (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the association between thigh circumference and risk of coronary artery disease. Study Design: Case-control study: Place and duration of study: Department of Medicine, CMH Hospital Multan, Pakistan from November 2023 to February 2024. Methods: A total of 150 patients reporting at the outpatient department and diagnosed as having coronary artery disease were enrolled in this study and included in Study group through consecutive sampling. Another 150 patients reporting at the outpatient department and not suffering from coronary artery disease were included in the Control group. Diagnosis of coronary artery disease was performed on the basis of electrocardiogram, levels of creatine kinase and further confirmed on coronary angiogram. All the demographic details and relevant clinical history and anthropometric measurements were performed including the thigh circumference. The primary outcome was set as the significance of difference between thigh circumferences of patients in the Study group compared with patients in Control group. Results: The Mean±SD of age of study participants was 55.23±8.12 years with age ranging from 42 to 68 years. Male gender was 56% while female gender was 44%. The results of this study showed that thigh circumference in Study group was significantly smaller than that in Control group (51.30±3.41 cm Vs 52.55±3.80 cm, p=0.003). Moreover the number of patients with thigh circumference≤50 cm were significantly higher in the Study group compared to Control group (58 Vs 40, p=0.026). Conclusion: An association was found between smaller thigh circumference and incidence of coronary artery disease, it is therefore an important anthropometric parameter for measuring the risk of coronary artery disease.